Physical therapy improves motion in a patient with inclusion body myositis - a case report - Stevanović Jelena; Vulović Maja; Pavićević Danijela; Bezmarević Mihailo; Stojković Anđelka; Radunović Aleksandar; Aksić Miljana; Milošević Bojan; Cvetković Aleksandar; Jovanović Milan; Ivošević Anita (Vojnosanitetski Pregled, 2020)
Introduction. Inclusion body myositis (IBM) is a rare form of inflammatory myopathy with a slowly progressive course. It is manifested by early weakness and atrophy of skeletal muscles, especially forearm muscles and the quadriceps. At the very beginning of the disease, clinical symptoms are not pronounced, therefore it is difficult to diagnose. Case report. A forty-eight-year-old female patient visited her doctor due to the weakness of muscles in arms and legs. Five years prior to this, she was treated by a neurologist and a physiatrician on several occasions with different diagnoses for progressive muscle weakness. During the last hospitalization, IBM was diagnosed after the muscle biopsy findings. After the diagnosis, the patient underwent intensive physical therapy in order to preserve the ability to independently perform everyday activities and stability of walk. Conclusion. IBM is a rare clinical entity which often takes several years to be diagnosed. Progressive muscle weakness in elderly should point to possible IBM diagnosis, which is only confirmed by muscle biopsy. Physical therapy has a significant role in the treatment as it leads to improvement of functional abilities of the patients in their daily activities, thus reducing the disability degree.